The Influence of Training, Compensation, and Work Discipline on Employee Performance at PT. Vemrer Jaya Abadi Medan: The Influence of Training, Compensation, and Work Discipline on Employee Performance at PT. Vemrer Jaya Abadi Medan - Cut Fitri Rostina; Koko Mariani Harianja; Febiguellen Febiguellen; Jullius Dwi Tantyo (Jurnal Mantik, 2020)
The purpose of this study is to examine and analyze the effect of training, compensation, and work discipline on the performance of employees of PT Vemrer Jaya Abadi Medan. The decline in employee performance is due to employee training, work compensation that is not in accordance with low employee work discipline. The sample in this study amounted to 72 employees. The research method uses multiple linear regression analysis techniques. The conclusion in this study shows that partially Training, Work Compensation and Work Discipline have a positive and significant effect on the Employee Performance of PT Vemrer Jaya Abadi Medan. Simultaneously Training, Work Compensation and Work Discipline have a positive and significant effect on Employee Performance of PT Vemrer Jaya Abadi Medan